Bounds of Degree-Based Molecular Descriptors for Generalized F-sum Graphs - Jia Bao Liu; Sana Akram; Muhammad Javaid; Abdul Raheem; Roslan Hasni (Discrete Dynamics in Nature and Society)
A molecular descriptor is a mathematical measure that associates a molecular graph with some real numbers and predicts the various biological, chemical, and structural properties of the underlying molecular graph. Wiener (1947) and Trinjastic and Gutman (1972) used molecular descriptors to find the boiling point of paraffin and total π-electron energy of the molecules, respectively. For molecular graphs, the general sum-connectivity and general Randić are well-studied fundamental topological indices (TIs) which are considered as degree-based molecular descriptors. In this paper, we obtain the bounds of the aforesaid TIs for the generalized F-sum graphs. The foresaid TIs are also obtained for some particular classes of the generalized F-sum graphs as the consequences of the obtained results. At the end, 3 D-graphical presentations are also included to illustrate the results for better understanding.